Purchasing and supply management (McGraw-Hill, 2002)
Purchasing and Supply Management, 12th Edition, recognizes the major supply challenges facing all organizations and their purchasing and supply management implications. It also provides solid grounding in the basic tools and techniques along with opportunities to test comprehension through carefully crafted questions and cases